Analysis of Construction Risk Factors Affecting Traffic Flow Performance at Gaforaya Roundabout near Four Points Hotel - Putra Palsamu, Andantino; Fikri, Aulia; Pramana, Widianto Eka; Fahlevi, Erdin (Fakultas Teknik Universitas Tanjungpura, 2026)
Urban construction activities often generate disturbances that affect surrounding traffic performance, particularly when projects are located near major road intersections. This study aims to identify and analyze construction-related risks associated with the Four Points Hotel development in Kubu Raya and evaluate their impact on traffic flow performance at the Gaforaya Roundabout along Ahmad Yani II Road. A quantitative approach was applied using primary data obtained from field surveys, including traffic volume and side-friction observations conducted in 2024. Multiple linear regression analysis was conducted in SPSS to examine the influence of several construction risk factors: project vehicle frequency, material loading and unloading activities, lane narrowing, working duration, and traffic management arrangements. The results indicate that traffic management is the most influential factor affecting traffic volume variation, accounting for 11.3% of the regression model. The highest observed traffic volume reached 1,960.6 passenger car units per hour during the weekend peak period. These findings highlight the importance of effective temporary traffic management strategies to minimize construction-related disruptions to urban traffic flow.